Biology of Trypanosoma cruzi: An update Biología del Trypanosoma cruzi: Actualización - André Vianna Martins; Andréia Patrícia Gomes; Eduardo Gomes de Mendonça; Juliana Lopes Rangel Fietto; Luiz Alberto Santana; Maria Goreti de Almeida Oliveira; Mauro Geller; Ramon de Freitas Santos; Rodrigo Roger Vitorino; Rodrigo Siqueira-Batista (Asociación Colombiana de Infectología, 2012)
Chagas disease, an illness caused by the protozoan Trypanosoma cruzi, is clinically and epidemiologically important in Latin America, and particularly in Brazil. This article presents the main biological characteristics of Trypanosoma cruzi, emphasizing ultrastructural, morphological, evolutionary, transcriptomic, and proteomic aspects. With this purpose a literature review was conducted, which allowed for the construction of different sections of the text. The efforts to expand the knowledge of this protist biology may bring positive implications for the understanding of the pathogenesis, control, and above all, treatment of patients affected by this disease. A moléstia de Chagas, enfermidade causada pelo protozoário Trypanosoma cruzi, apresenta grande relevância clínica e epidemiológica na America Latina, com destaque para o Brasil. Neste artigo serão apresentadas as principais características biológicas do Trypanosoma cruzi, enfatizando-se os aspectos ultra-estruturais, morfológicos, evolutivos, transcriptômicos e proteômicos. Para tanto, foi realizada revisão da literatura, a qual subsidiou a construção de diferentes seções do texto. As investidas para ampliar o conhecimento acerca da biologia do protista poderão trazer implicações positivas para a compreensão da patogênese, do controle e, sobretudo, do tratamento dos pacientes portadores da moléstia.